The relationship between verbal form and event structure in sign languages. Issue 1 (11th November 2019) - Davidson, Kathryn; Kocab, Annemarie; Sims, Andrea D.; Wagner, Laura
Abstract : Whether predicates describe events as inherently bounded (telic) or unbounded (atelic) is usually understood to be an emergent property that depends on several factors; few, if any, spoken languages have dedicated morphology to mark the distinction. It is thus surprising that sign languages have been proposed to have dedicated morphology for telicity, and moreover that it takes a form which iconically reflects the underlying event structure – this is known as the "Event Visibility Hypothesis" (EVH) (Wilbur 2008 ). The EVH has been extended with claims about its universality in sign languages (Wilbur 2008 ; Malaia & Wilbur 2012 ), its gradient nature (Kuhn 2017 ), and its iconic transparency (Strickland et al. 2015 ). However, in this paper we argue that the status of this relationship between form and meaning remains an open question due to (a) lack of independent tests for telicity, (b) lack of lexical coverage, (c) lack of demonstration that formal expressions of telicity are morphological in nature, rather than a lexical property, and (d) inability to sufficiently dissociate telicity and perfectivity. We present new data coming from verbs that alternate in both form and meaning in ASL that is in line with the EVH, and conclude that while there is evidence supporting a morphological marker, the proposed form and telicity are not isomorphic in their distribution, significantly limiting the "visibility" of the event structure. We further propose that much of the related iconicity is the result of several independent factors also found in spoken languages, so that sign languages may be more similar to spoken languages than typically implied in this domain.